Pengembangan Aplikasi E-School Dengan Pendekatan Evolutionary Prototype Studi Kasus SMP Negeri 1 Cikarang Barat - Alawiyah Nurmala; Bayu Priyambadha; Denny Sagita Rusdianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Technology development nowdays has reached all areas including education.With the support of technology, teaching and learning activities can be increase to a better level. SMP Negeri 1 Cikarang Barat has adequate technology facilities, but the facility is not fully utilized yet for teaching and learning activities. In this research, developed a learning application called E-School which has a feature to detect plagiarism on the answers of tasks and student quizzes which type is essay. The plagiarism detection feature will be developed by applying knuth-morris-pratt algorithm. The application applying the Evolutionary Prototype approach that could be help stakeholders and system developers in exploring system requirement specification as desired by stakeholder. By applying Evolutionary Prototype approch,. stakeholders can work together as to what will be developed and this will impact some additional and functional changes between the first prototype and the second prototype. Stakeholder and developer can evaluated the prototype of the application that is being developed, this can be simplify the communication in the aim for system elicitation and this can avoid some of misunderstanding between stakeholder and developer in builiding application. The results of the test obtained all the functionality contained in the application first prototype and second prototype has been running well and the second prototype can be used by stakeholder.